THE REPRESENTATION OF WOMAN’S OPPRESSION IN LISA SEE’S SNOW FLOWER AND THE SECRET FAN - Azara Nafia Irmadani; Supiastutik Supiastutik; Irana Astutiningsih (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2019)
Snow Flower and The Secret Fan is one type of fiction novel written by Lisa See in 2005. Snow Flower and The Secret Fan tells about the lives of Chinese women in the nineteenth century where women's position was lower than men. In that era, there was a tradition that required women to tie their legs when they were young then caused them to endure unbearable pain because of a leg tie. By tying their legs, they can get married and improve their social status and bring them to a better life. Legs bound are to be sexually pleasure for men to achieve sexual satisfaction. In addition, in that era women were not permitted to get education like men. This problem was the impact of the Patriarchal culture. In the Patriarchal culture, there is a Confucian teaching that is used as a way of life for Chinese people. The teaching requires women to obey men: Father, husband, and later their sons. Therefore, Chinese women live as a second-class. In conducting this research, the author uses Representation Theory by Stuart Hall. Research shows that female oppression is clearly illustrated in the novel through a leg tie. Lisa See realistically describes the real conditions of women's oppression in China in the Snow Flower novel and The Secret Fan.